Determining medical decision-making capacity in brain tumor patients: why and how?. Issue 6 (16th July 2020) - Pace, Andrea; Koekkoek, Johan A F; van den Bent, Martin J; Bulbeck, Helen J; Fleming, Jane; Grant, Robin; Golla, Heidrun; Henriksson, Roger; Kerrigan, Simon; Marosi, Christine; Oberg, Ingela; Oberndorfer, Stefan; et al.
Abstract: Background: Brain tumor patients are at high risk of impaired medical decision-making capacity (MDC), which can be ethically challenging because it limits their ability to give informed consent to medical treatments or participation in research. The European Association of Neuro-Oncology Palliative Care Multidisciplinary Task Force performed a systematic review to identify relevant evidence with respect to MDC that could be used to give recommendations on how to cope with reduced MDC in brain tumor patients. Methods: A literature search in several electronic databases was conducted up to September 2019, including studies with brain tumor and other neurological patients. Information related to the following topics was extracted: tools to measure MDC, consent to treatment or research, predictive patient- and treatment-related factors, surrogate decision making, and interventions to improve MDC. Results: A total of 138 articles were deemed eligible. Several structured capacity-assessment instruments are available to aid clinical decision making. These instruments revealed a high incidence of impaired MDC both in brain tumors and other neurological diseases for treatment- and research-related decisions. Incapacity appeared to be mostly determined by the level of cognitive impairment. Surrogate decision making should be considered in case a patient lacks capacity, ensuring that the patient's "best interests" and wishes are guaranteed. Several methods are available that may help to enhance patients' consent capacity. Conclusions: Clinical recommendations on how to detect and manage reduced MDC in brain tumor patients were formulated, reflecting among others the timing of MDC assessments, methods to enhance patients' consent capacity, and alternative procedures, including surrogate consent.